2022
DOI: 10.3390/ani12151970
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Evolution of Aphid Mitogenome Features from New Data and Comparative Analysis

Abstract: The complete mitochondrial genomes and their rearrangement patterns can provide useful information for inferring evolutionary history of organisms. Aphids are one of the insect groups with some unique mitogenome features. In this study, to examine whether some features in aphid mitogenomes are independent species-specific evolutionary events or clade-specific events at certain taxonomic levels, we sequenced three new aphid mitogenomes (Hormaphidinae: Ceratovacuna keduensis, Pseudoregma panicola; Lachninae: Nip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 84 publications
(69 reference statements)
1
8
0
Order By: Relevance
“…In the past two decades, the mitochondrial genome emerged as important molecular data for higher-level phylogenetic analyses ( Saccone et al 1999 ; Timmermans et al 2010 , 2016 ; Cameron 2014 ; Li et al 2015 ; Qin et al 2015 ; Nie et al 2020 , 2021 ; Motyka et al 2022 ; Zheng et al 2022 ), evolutionary strategies ( Krzywinski et al 2011 ; Nie et al 2019 ; Motyka et al 2022 ; Zhang et al 2022 ), and genetic diversity analyses ( Lim et al 2021 ). The buprestid mitogenome also caught the attention of taxonomists.…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades, the mitochondrial genome emerged as important molecular data for higher-level phylogenetic analyses ( Saccone et al 1999 ; Timmermans et al 2010 , 2016 ; Cameron 2014 ; Li et al 2015 ; Qin et al 2015 ; Nie et al 2020 , 2021 ; Motyka et al 2022 ; Zheng et al 2022 ), evolutionary strategies ( Krzywinski et al 2011 ; Nie et al 2019 ; Motyka et al 2022 ; Zhang et al 2022 ), and genetic diversity analyses ( Lim et al 2021 ). The buprestid mitogenome also caught the attention of taxonomists.…”
Section: Introductionmentioning
confidence: 99%
“…A non-coding element containing initiation sites for replication and transcription is called the A + T rich region (CR) [ 12 , 13 ]. With the great developments in PCR techniques and high-throughput sequencing, many animal group’s complete mitogenomic data including insects are easier to obtain and have been widely applied in the research of phylogenetics, molecular evolution, evolutionary and comparative genomics, and population genetics [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gene rearrangement has been extensively reported in various insect mitogenomes [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. The most common type of gene arrangement involves tRNA genes, among which the gene orders in Hymenoptera, Thysanoptera, Psocoptera, Hemiptera, and Phthiraptera exhibit more frequent rearrangements than the putative ancestral gene order [ 7 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Some studies have suggested that mitogenome rearrangement may provide essential clues regarding evolution and origin [ 2 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%